2017
DOI: 10.1667/rr0010cc.1
|View full text |Cite
|
Sign up to set email alerts
|

Germicidal Efficacy and Mammalian Skin Safety of 222-nm UV Light

Abstract: We have previously shown that 207-nm ultraviolet (UV) light has similar antimicrobial properties as typical germicidal UV light (254 nm), but without inducing mammalian skin damage. The biophysical rationale is based on the limited penetration distance of 207-nm light in biological samples (e.g. stratum corneum) compared with that of 254-nm light. Here we extended our previous studies to 222-nm light and tested the hypothesis that there exists a narrow wavelength window in the far-UVC region, from around 200–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
293
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 273 publications
(313 citation statements)
references
References 51 publications
14
293
1
5
Order By: Relevance
“…For comparison, using a similar experimental arrangement, but using a conventional 254 nm germicidal UVC lamp, McDevitt et al 19 found a D95 value of 1.1 mJ/cm 2 (95% CI: 1.0–1.2) for H1N1 virus. Thus as we 13,15 and others 1618 reported in earlier studies for bacterial inactivation, 222-nm far-UVC light and 254-nm broad-spectrum germicidal light are quite similar in their efficiencies for viral inactivation, the comparatively small differences presumably reflecting differences in nucleic acid absorbance. However as discussed above, based on biophysical considerations and in contrast to the known human health safety issues associated with conventional germicidal 254-nm broad-spectrum UVC light, far-UVC light does not appear to be cytotoxic to exposed human cells and tissues in vitro or in vivo 1315 .…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…For comparison, using a similar experimental arrangement, but using a conventional 254 nm germicidal UVC lamp, McDevitt et al 19 found a D95 value of 1.1 mJ/cm 2 (95% CI: 1.0–1.2) for H1N1 virus. Thus as we 13,15 and others 1618 reported in earlier studies for bacterial inactivation, 222-nm far-UVC light and 254-nm broad-spectrum germicidal light are quite similar in their efficiencies for viral inactivation, the comparatively small differences presumably reflecting differences in nucleic acid absorbance. However as discussed above, based on biophysical considerations and in contrast to the known human health safety issues associated with conventional germicidal 254-nm broad-spectrum UVC light, far-UVC light does not appear to be cytotoxic to exposed human cells and tissues in vitro or in vivo 1315 .…”
Section: Discussionsupporting
confidence: 73%
“…We have developed an approach to UV-based sterilization using single-wavelength far-UVC light generated by filtered excilamps, which selectively inactivate microorganisms, but does not produce biological damage to exposed mammalian cells and tissues 1315 . The approach is based on biophysical principles in that far-UVC light can traverse and therefore kill bacteria and viruses which are typically micrometer dimensions or smaller, whereas due to its strong absorbance in biological materials, far-UVC light cannot penetrate even the outer dead-cell layers of human skin, nor the outer tear layer on the surface of the eye.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…UV-C radiation is effective for inactivating protozoa, bacteria, viruses, and many microorganisms. According to literature [17][18][19][20][21], the use of UV-C radiation is especially a good, environment-friendly, and chemical-free method to inactivate dangerous pathogens in diverse condition. UV-C cannot pass through our atmosphere, so it does not contribute to DNA damage.…”
Section: Nonlinear Models Of Molecule Interaction With Short-pulse Ramentioning
confidence: 99%